Synthesis of Chitosan based nanoemulsions and their characterization and antifungal activity toward fungi causing mucormycosis - Mohamed S. Hasanin; Fathallah A. Ayoob; Amr H. Hashem; Mahmoud Emam (Scientific Reports)
Abstract Aromatic plants produce essential oils (EOs) with diverse phytochemicals and biological applications. This study investigated three eco-friendly nanoemulsions of Lemon peel (LPO), Turmeric (TO), and Black seed (BSO) oils loaded into nanochitosan (NCh) for their antifungal activity against resistant fungal strains. Phytochemical analysis identified oxygenated/non-oxygenated hydrocarbons and saturated/unsaturated fatty acids in the EOs. Physicochemical characterization using FTIR, DLS, and HR-TEM showed stable nanoemulsions and nanochitosan with homogeneous particle size distributions in the nanoscale range. Notably, the essential oil nanoemulsions exhibited potent antifungal activity against Mucor racemosus, Rhizopus microsporus, and Lichtheimia corymbifera, resistant to commercial antifungal drugs. The nanoemulsions loaded with 1–3% chitosan showed inhibition zones ranging from 17 to 23 mm, outperforming the synthetic antifungal treatments. These findings highlight the potential of plant-derived essential oil nanoemulsions loaded into biocompatible nanochitosan as a promising, sustainable alternative to combat the growing threat of invasive fungal infections and drug resistance. Incorporating natural, eco-friendly materials enhances the stability, bioavailability, and targeted delivery of the active phytochemicals, contributing to the antifungal solution’s overall efficacy and safety profile.